Crystallization and preliminary X‐ray analysis of the periplasmic domain of FliP, an integral membrane component of the bacterial flagellar type III protein‐export apparatus. Issue 9 (1st September 2014) - Fukumura, Takuma; Furukawa, Yukio; Kawaguchi, Tatsuya; Saijo‐Hamano, Yumiko; Namba, Keiichi; Imada, Katsumi; Minamino, Tohru
<x xml:space="preserve">Abstract</x> The bacterial flagellar proteins are transported via a specific export apparatus to the distal end of the growing structure for their self‐assembly. FliP is an essential membrane component of the export apparatus. FliP has an N‐terminal signal peptide and is predicted to have four transmembrane (TM) helices and a periplasmic domain (FliPP) between TM‐2 and TM‐3. In this study, FliPP from Thermotoga maritima (TmFliPP) and its selenomethionine derivative (SeMet‐TmFliPP) were purified and crystallized. TmFliPP formed a homotetramer in solution. Crystals of TmFliPP and SeMet‐TmFliPP were obtained by the hanging‐drop vapour‐diffusion technique with 2‐methyl‐2, 4‐pentanediol as a precipitant. These two crystals grew in the hexagonal space group P6222 or P6422, with unit‐cell parameters a = b = 114.9, c = 193.8 Å. X‐ray diffraction data were collected from crystals of TmFliPP and SeMet‐TmFliPP to 2.4 and 2.8 Å resolution, respectively.